Perspectives of Moroccan EFL Students on Collaborative Writing: The Case of Hassan II University - Mohamed Choujaa; Nadia Hellalet; Mouhssine Echcharfy (Yayasan Visi Intan Permata, 2026)
The need for transformative pedagogies is growing due to limitations inherent in lecture-based teaching. Collaborative learning is an excellent method for addressing some of these shortcomings. Collaboration provides ways that can be used by both instructors and students as they work together to develop content and facilitate student engagement through discussion and problem-solving. This will potentially enhance the sense of criticality in Moroccan EFL university students’ written texts. Therefore, the study’s objective is to investigate the benefits of collaborative writing from the perspective of Moroccan EFL University students. To accomplish this goal, a mixed-methods research design was employed using questionnaire data to obtain quantitative information and follow-up semi-structured interview data to provide qualitative insight into the responses. Convenience sampling was used to select 140 English majors from Hassan II University in Casablanca. The findings demonstrated that Moroccan Hassan II University EFL students recognized the significance of using collaborative, argumentative writing. The students argued that group writing allows them to discuss, exchange perspectives, share the workload, and learn from peer feedback. Nonetheless, writing collaboratively can be difficult for some participants, especially because it can involve communication problems, a lack of interest, and uneven participation. These difficulties pushed some respondents to sometimes prefer individual writing instead. Several implications for ensuring high-quality outcomes will be drawn from the results obtained